MODUL AJAR BERBASIS PROBLEM BASED LEARNING DENGAN PEMBELAJARAN MENDALAM MATERI RASIO UNTUK MEMFASILITASI KEMAMPUAN PEMAHAMAN MATEMATIS MURID FASE D - Naswa Jumeli Putri; Rini Dian Anggraini; Kartini (Jurnal Ilmiah Matematika Realistik, 2026)
This study was conducted to facilitate students’ mathematical understanding, which remains relatively low. Students experience difficulties in understanding mathematics due to irregular learning habits and the use of instructional methods that are less engaging. The aim of this research was to create a Problem Based Learning (PBL) based teaching module with a deep learning approach on ratio material to facilitate the mathematical understanding of Phase D students, and to examine its validity and practicality. The ADDIE model analysis, design, development, implementation, and evaluation was used in this study's development research design. The module was validated by three expert validators and achieved a validation score of 94.71, demonstrating a highly valid category. The test of practicality conducted by teachers resulted in a score of 93.58, categorized as very practical. Furthermore, the small-group trial obtained a score of 88.47 and the large-group trial obtained a score of 86.27, both of which met the practical criteria. These findings support the validity and usefulness of the PBL based teaching module with a deep learning strategy on ratio content for enhancing Phase D students' mathematics comprehension.